Smaller sizes of polyethylene terephthalate microplastics mainly stimulate heterotrophic N2O production in aerobic granular sludge systems - Yingrui Liu; Yanying He; Qian Lu; Tingting Zhu; Yufen Wang; Yindong Tong; Yingxin Zhao; Bing-Jie Ni; Yiwen Liu (Water Research X)
Widespread polyethylene terephthalate microplastics (PET MPs) have played unintended role in nitrous oxide (N2O) turnovers (i.e., production and consumption) at wastewater treatment plants (WWTPs). Mainstream aerobic granular sludge (AGS) systems possess potentially strong N2O-sink capability, which may be reduced by PET MPs stress through altering N2O-contributing pathways, electron transfer, and microbial community structures. In this study, the effects of PET MPs with two common particle sizes of effluent from WWTPs (0.1 and 0.5 mm) on N2O turnovers, production pathways and N2O-sink capability were systematically disclosed in AGS systems by a series of biochemical tests and molecular biological means to achieve the goal of carbon neutrality. The results indicated that 0.1 mm PET MPs could more significantly stimulate N2O production in AGS systems by inhibiting denitrifying metabolism, compared with control and 0.5 mm PET MPs systems. Specifically, 0.1 mm PET MPs slightly increased the relative abundance of Nitrosomonas, reducing N2O yields via promoting the hydroxylamine (NH2OH) oxidation pathway during nitrification. Also, 0.1 mm PET MPs inhibited the electron transport system activities and the relative abundance of N2O reductase, hindering N2O reduction during denitrification. Most importantly, 0.1 mm PET MPs more apparently reduced the N2O-sink capability based on the ratio of N2O reductase gene and nitrite reductase gene.